Climate trends in the Cape Town area, South Africa - Mark R Jury (Water SA, 2020)
Climatic conditions near Cape Town, South Africa (34°S, 19°E) are analysed for historical trends in station measurements in the 20th century and in modern satellite-blended datasets. Despite the variety of datasets and record lengths, all show a steady drying trend. Faster rates of warming, 0.1°C∙yr-1, are found in land surface temperatures during the period 2000–2017. Drying trends are most acute to the northwest of the Hottentots Holland mountains. Hydrology station measurements in the Upper Berg River catchment since 1956 reveal a decline in streamflow of −0.012 m3∙s-1∙month-1, and an upward slope in potential evaporation of +0.020 W∙m-2∙month-1. Rainfall has declined most in May and September, indicating a shorter winter wet season. Features supporting the drying trend include an increase of easterly winds and low-level subsidence during summer. The clockwise circulation trend around Cape Town entrains dry air from the Karoo interior and the south coast upwelling zone, leading to negative sensible heat flux, a capping inversion and diminished orographic rainfall.